Strategising Malaysian Defence Budgeting During Economic Recessions - Amirudin Sulaiman , Mohd Zaini Salleh , Ananthan, S , Wong Wai Loong , Syafina Darlila Ahmad Jaidi (International Journal of Advanced Science and Technology, 2020)
Economic recessions and financial crises can have a direct impact on a country’s defence budget and its subsequent defence expenditure. It is about striking a proportion of the country’s national income for socio-economic development and defence so as not to compromise the country’s integrity and sovereignty. The aims of this study are: (1) To analyse the defence budgets and defence expenditures for Malaysia; (2) To analyse the operating and development expenditures in the defence budget for Malaysia. This study applies a content analysis from the data compiled including relevant secondary sources for both the aims of this study. The study reveals that there are defence budget cuts due to economic recessions, the 1997 financial crisis, 2008 recession and the 2014 oil price crisis. Operating expenditures are on the rise as compared to development expenditures. As such, there is a need for budgetary and financial strategies astuteness contributing towards the continued sustainment of the Malaysian Armed Forces (MAF) capabilities and readiness including its longer-term strategic developmental plan to ensure its development can continue unabated during economic recessions or financial crises. Additionally, to ensure that the country’s future security and defence needs can be met objectively.